PROFIL KEMAMPUAN MATEMATIKA MAHASISWA PERBANKAN SYARIAH DENGAN STRUCTURAL EQUAUATION MODELING (SEM) - Any Tsalasatul Fitriyah (IQTISHADUNA, 2018)
The aim of this research was to analyzed mathematical abilities of university student at the islamic banking department with factors of mathematical abilities. Factors of mathematical abilities in this research limited from educational background, learning interests, and study habits. Analysis ini this research using Structural Equation Modeling (SEM). In this research study case at the State Islamic University of Mataram. The results of data analysis showed educational background had no effect on mathematical abilities. Learning interest has a significant effect with a coefficient 0.23 and t-value of 1.789. Variables of genuine attitude in learning activities which are indicators of interest learning have a significant effect with a coefficient of 0.39 and t-values of 2.11. While the learning habits variable on delay avoidan indicators (Timeliness of doing work) has an effect of 0.45 and t-value of 2.36. The work method variable also has an effect with a coefficient of 0.56 and a t-value of 2.12 which means it has a significant influence.